PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN E-LKPD TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK DI KELAS XII IPS SMA PERTIWI 1 PADANG - Oktavia, Israhmi (Jurnal Edukasi dan Penelitian Matematika, 2023)
Mathematics aims to educate problem solving and become a challenging subject in class XII social studies SMA Pertiwi 1 Padang. LKPD and Problem Based Learning (PBL) model were adopted to improve this ability. This pseudo-experiment used Nonequivalent Posstest-Only Control Group Design. Simple random sampling. Class XII IPS 1 and 3 as experimental class and control class. The final test analysis used t-test with P-Value = 0.013 to reject H0. Then, PBL with LKPD electronic solve mathematical problems better than the usual method. PBL model with LKPD has an effect on mathematical problem solving.Keywords– Mathemtical Problem Solving Ability, Problem Based Learning, Conventional Learning